The Rock Art Of Kinta Valley,Perak, Malaysia - Saw, Chaw Yeh (2022)
This dissertation investigates the rock art tradition of Peninsular Malaysia and explores its cultural affiliation, based on the rock art recorded in the Kinta Valley, Perak, Malaysia. Up until today, in-depth studies and international publications on rock art in Peninsular Malaysia were relatively scarce. This study presents the results of systematic documentation of eleven rock art sites, namely Gua Kelawar, Gua Mat Surat, Gua Mat Surat 2, Gua Tambun, Gua Tempurung, Gua Toh Semelah, Karang Besar Rock Shelter, Keroh Rock Shelter 1, Keroh Rock Shelter 2, Kintaly Rock Shelter 1, and Kintaly Rock Shelter 2. The documentation method differs from the earlier studies in which it incorporated a five-level motif categorization model to eliminate analytical bias. The rock art was later analysed using multivariate analysis (correspondence analysis and multidimensional scaling) with additional comparative study to identify the relationship between sites. Apart from the previously known rock art traditions, which had been broadly divided into coloured and black rock art traditions, this study had identified five rock art sub-traditions (ST 1 – 5) across the Kinta Valley. The study suggests that the earliest phase of rock art comprises two subtraditions (ST 1 & ST 2) which began as early as the Hoabinhian period (~13,000 years ago). Both ST 1 and ST 2 can be found at rock shelters or caves and represented by coloured rock art depicting geometric shapes and zoomorphic figures. The other three sub-traditions are made up of black rock art, with an occasional depiction of white rock art. While ST 5 is clearly of the contact period since it often includes foreign subject matter, ST 3 and ST 4 predominantly consist of designs attributed to the Orang Asli culture.